Observations of the Breakthrough Phase of Attachment Process in Laboratory Long Sparks. Issue 16 (26th August 2022) - Fu, Yufei; Chen, Weijiang; Zhao, Yushun; Ding, Lijian; Fu, Zhong; Xiang, Nianwen; Qiu, Xinjie; Gu, Jianwei; Pei, Zhehao; Zhang, Zhiyuan; Huang, Shengxin
Abstract: High‐speed video frames and discharge current records of 34 long laboratory sparks were examined. Two consecutive frames of the breakthrough phase, depicting the evolution of the common streamer zone, were obtained in five events, all presented in this study. Two types of luminous structures were observed inside the common streamer zone just before the return stroke phase: the floating luminous segment and the luminous channel linking the opposite polarity leaders. The luminous structure served as a selected route for the return stroke channel. These results demonstrate that the transformation of high‐impedance common streamer zone into a hot plasma channel may involve two main features: the common streamer zone shrinking and the dominant development of the selected route. Plain Language Summary: The breakthrough phase is the final stage of the attachment process in cloud‐to‐ground lightning and begins with the establishment of high‐impedance region (called common streamer zone) between tips of two oppositely charged channels (called leaders) developing from thundercloud and grounded object. The evolution of the breakthrough phase is still not fully understood and very rarely captured in optical images. Many basic lightning phenomena and mechanisms were discovered in long laboratory sparks. Here, we investigated the breakthrough phase in laboratory long sparks generated by rod‐to‐rod air gaps, using a high‐speed video camera and a synchronized electrical parameter measurement system. Two consecutive frames of the breakthrough phase, showing detailed evolution of the common streamer zone, were recorded for five events. Two types of unexpected luminous structures were captured between the two approaching oppositely charged leaders during the breakthrough phase, providing a new insight into the evolution of the breakthrough phase and improving our understanding of the lightning attachment process. Key Points: Two consecutive frames showing the breakthrough phase of attachment process were observed in five sparks Luminous structures were observed inside the common streamer zone just prior to the return stroke frame The observed luminous structure exhibits as the floating segment or the route linking the positive and negative leaders